2008
DOI: 10.2174/138161208784480090
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Interest of Adenosine A2A Receptors in Psychiatric Disorders

Abstract: The interest on targeting adenosine A 2A receptors in the realm of psychiatric diseases first arose based on its tight physical and functional interaction with dopamine D 2 receptors. However, the role of central A 2A receptors is now viewed as much broader than just controlling D 2 receptor function. Thus, there is currently a major interest in the ability of A 2A receptors to control synaptic plasticity at glutamatergic synapses. This is due to a combined ability of A 2A receptors to facilitate the release o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
150
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(155 citation statements)
references
References 273 publications
3
150
1
1
Order By: Relevance
“…The adenosinergic system can affect the efficiency of synaptic transmission and neurotransmitter release through a combined activation of inhibitory adenosine A 1 receptors and facilitatory adenosine A 2A receptors in neuronal circuits [28,29]. There is a growing body of evidence suggesting that these adenosine receptors could be promising therapeutic targets in a wide range of conditions, including neurodegenerative and psychiatric disorders such as major depression [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The adenosinergic system can affect the efficiency of synaptic transmission and neurotransmitter release through a combined activation of inhibitory adenosine A 1 receptors and facilitatory adenosine A 2A receptors in neuronal circuits [28,29]. There is a growing body of evidence suggesting that these adenosine receptors could be promising therapeutic targets in a wide range of conditions, including neurodegenerative and psychiatric disorders such as major depression [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Both receptors have a role in miscellaneous biological processes, particularly the cAMPprotein kinase A signaling cascade and the fine-tuning of glutamatergic information flow (Schiffmann et al, 2007;van Calker and Biber, 2005). They are considered to be modulators of glial function, neuronal communication and neuronal activity, and to be involved in sleep and arousal, and cognition, as well as different psychiatric disorders, including anxiety and other mood disorders (Ribeiro et al, 2003;Cunha et al, 2008;Freitag et al, 2010). In mice, genetic knockout of adenosine A 1 or A 2A receptors has been linked to increased anxiety (Ledent et al, 1997;Johansson et al, 2001), implicating the corresponding genes or, more precisely, polymorphisms within these genes, as promising candidates for increased anxiety reactions.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds proved to be the most active members in our study. 16,17,22,23,26, 29 and 30 showed 20-37% reduction in serum glucose level. Structureactivity correlation among this series showed that the type of phthalimide and/or benzamide functionality is crucial for activity as presented by compound 24 (theophylline-diimide 56%) Figure 1.…”
Section: Structure-activity Correlationmentioning
confidence: 94%
“…Fundamental signs of diabetes mellitus such as hyperglycemia, loss of body weight, polyphagia and polydipsia were induced in rats by injection of streptozotocin [17][18][19] . Subsequently, animals were treated with the compounds under test and glibenclamide as a positive control.…”
Section: Hypoglycemic Activitymentioning
confidence: 99%
See 1 more Smart Citation